2021
DOI: 10.1021/acsami.1c12176
|View full text |Cite
|
Sign up to set email alerts
|

Green Nanoparticle Scavengers against Oxidative Stress

Abstract: The usage of exogenous antioxidant materials to relieve oxidative stress offers an important strategy for the therapy of oxidative stress-induced injuries. However, the fabrication processes toward the antioxidant materials usually require the involvement of extra metal ions and organic agents, as well as sophisticated purification steps, which might cause tremendous environmental stress and induce unpredictable side effects in vivo. To address these issues, herein, we proposed a novel strategy to fabricate gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 56 publications
0
30
0
Order By: Relevance
“…In particular, the excellent UV absorption and antioxidant capacity, as well as bioadhesion, antibacterial and other auxiliary functions make polyphenols possess great potential in the design and preparation of safe and robust green sunscreens. [44][45][46][47][48][49][50][51][52][53][54][55] For example, natural plateau plants could protect themselves against extra-intense UV irradiation due to the presence of abundant polyphenolic components such as salidroside in Rhodiola rosea and caulis dendrobii polyphenols in Dendrobium officinale. 56,57 A plateau is the main locality for tea growth and local people have utilized tea products rich in tea polyphenols to resist UV irradiation since the ancient times.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the excellent UV absorption and antioxidant capacity, as well as bioadhesion, antibacterial and other auxiliary functions make polyphenols possess great potential in the design and preparation of safe and robust green sunscreens. [44][45][46][47][48][49][50][51][52][53][54][55] For example, natural plateau plants could protect themselves against extra-intense UV irradiation due to the presence of abundant polyphenolic components such as salidroside in Rhodiola rosea and caulis dendrobii polyphenols in Dendrobium officinale. 56,57 A plateau is the main locality for tea growth and local people have utilized tea products rich in tea polyphenols to resist UV irradiation since the ancient times.…”
Section: Introductionmentioning
confidence: 99%
“…Due to this issue, many efforts have been devoted to engineer polyphonic materials with enhanced antioxidant properties that can achieve RONS depletion rapidly due to their abundant phenolic groups. [164][165][166] For instance, our group has demonstrated that the incorporation of PDA nanoparticles in dextran hydrogels could efficiently eliminate the ROS at the site of infected wounds, and further promote wound closure compared to the pure hydrogel group. 167 In another study, Cao and co-workers fabricated a TA-coated substrate, which could capture ROS efficiently.…”
Section: Interfacial Electroconductive Propertymentioning
confidence: 99%
“…A photothermal antibacterial platform composed of coated curcumin (Cur) nanocrystals can treat diabetic wounds infected with methicillin-resistant Staphylococcus aureus (MRSA) through an M2 (macrophage) Mφ polarization strategy [ 159 ]. In an acute kidney injury model, these green nanoparticle (tea polyphenol) scavengers can effectively prevent intracellular oxidative damage, accelerate wound healing, and protect kidneys from reactive oxygen species [ 160 ].…”
Section: Application Of Mofs In Wound Healingmentioning
confidence: 99%
“…Therefore, Chen et al encapsulated TP in a PVA/alginate hydrogel (TPN@H) and demonstrated that TPN@H could promote wound healing in diabetic rats by regulating the PI3K/AKT signaling pathway [ 166 ]. Peng et al developed a green nanoparticle scavenger against oxidative stress based on TP, which effectively prevented intracellular oxidative damage and accelerated wound recovery [ 160 ]. A recent study utilized C-confined CoOx NPs to mimic peroxidase enzymatic activity to scavenge hydroxyl radicals [ 167 ].…”
Section: Application Of Mofs In Wound Healingmentioning
confidence: 99%